Pelatihan Pembuatan Website Memanfaatkan Wix Untuk Blog Pribadi Pada Siswa SMAN 2 Gunung Talang: Website Development Training Using Wix for Personal Blogs for Students of SMAN 2 Gunung Talang - Fathan Surya Hamdi; Idria Maita (Institut Riset dan Publikasi Indonesia, 2022)
In the current digitalization era, it is necessary to be familiar with technology in addition to current developments.Even though they are miles away from where we are, humans can now quickly exchange information.The development of technology that makes human work easier has made this possible.Technological developments began with the development of the internet.The Internet is a global network of computers that can connect all computer users in networks all over the world to quickly and accurately exchange data and observations.As a result, students at SMAN 2 Gunung Talang must also be able to present articles, information, or news in order to learn how to create a website. However, students are not just readers of information.Students can also create opportunities and provisions for global content creators.